Youtube's Automated Translation and Google Translate: Possible Problems and Solutions - Alvin Taufik (Journal of English Language and Culture, 2018)
Translation technology has now been acknowledged as a subdomain of translation studies (Christensen, Flanagan, and Schjoldager, 2017). The researches on translation technology cover a lot of aspects of translation as well as the technology that is used to aid the process. This research is focused on the latter, especially on the results of the Human-aided Machine Translation (HAMT). The HAMT which becomes the focus of this research are Youtube’s Automated Translation and Google Translate (AT and GT respectively). The aim of this research is to evaluate the HAMTs, identify the problems, and propose a possible solution for the problems. This research is using a realism approach because it uses the translator students’ perspective of the HAMT, and the use of corpora. Questionnaires and experiments will be given and performed to assess and to formulate the solutions. Keywords:  HAMT, GT, AT, realism, corpora